2013
DOI: 10.1242/dev.100339
|View full text |Cite
|
Sign up to set email alerts
|

A time delay gene circuit is required for palp formation in the ascidian embryo

Abstract: The ascidian larval brain and palps (a putative rudimentary placode) are specified by two transcription factor genes, ZicL and FoxC, respectively. FGF9/16/20 induces ZicL expression soon after the bipotential ancestral cells divide into the brain and palp precursors at the early gastrula stage. FGF9/16/20 begins to be expressed at the 16-cell stage, and induces several target genes, including Otx, before the gastrula stage. Here, we show that ZicL expression in the brain lineage is transcriptionally repressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 30 publications
1
56
0
Order By: Relevance
“…The notochord developmental program was ectopically activated in Prdm1-r.a/b/Hes.a morphants We previously showed that Zic-r.b is precociously expressed in bipotential brain/palp progenitors at the 64-cell stage in doublemorphant embryos of Prdm1-r.a and Prdm1-r.b (Prdm1-r.a/b morphants), and this ectopic activation of Zic-r.b converts palp fate into brain fate (Ikeda et al, 2013). We also showed that Zic-r.b expression begins earlier (at the 32-cell stage) in Prdm1-r.a/b/Hes.a triple morphants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The notochord developmental program was ectopically activated in Prdm1-r.a/b/Hes.a morphants We previously showed that Zic-r.b is precociously expressed in bipotential brain/palp progenitors at the 64-cell stage in doublemorphant embryos of Prdm1-r.a and Prdm1-r.b (Prdm1-r.a/b morphants), and this ectopic activation of Zic-r.b converts palp fate into brain fate (Ikeda et al, 2013). We also showed that Zic-r.b expression begins earlier (at the 32-cell stage) in Prdm1-r.a/b/Hes.a triple morphants.…”
Section: Resultsmentioning
confidence: 99%
“…Three transcriptional repressors, Prdm1-r.a (formerly BZ1), Prdm1-r.b (formerly BZ2) and Hes.a are important for ensuring that Foxa.a and Zic-r.b are expressed sequentially in the presumptive brain cells, as indicated by the fact that Zic-r.b is precociously expressed at the 32-cell stage in triple morphants of Prdm1-r.a, Prdm1-r.b and Hes.a (Prdm1-r.a/b/Hes.a morphants) (Ikeda et al, 2013). In the present study, we show that Prdm1-r.a also promotes termination of Foxa.a expression, and we propose a robust mechanism for temporally distinct expression of Foxa.a and Zic-r.b to ensure the brain lineage specification.…”
Section: Introductionmentioning
confidence: 99%
“…Btd (also known as Sp8 or ZF220) is expressed in the palp lineage at the early tailbud stage, downstream of FoxC, the earliest marker of the palp lineage (Ikeda et al, 2013;Imai et al, 2004Imai et al, , 2006. In late tailbud embryos, Btd appears to be co-expressed with Emx in the rings, and also occurs in the intervening anterior-most ectoderm, but is specifically excluded from the center of the rings (Fig.…”
Section: Emx Buttonhead and Islet Mark The Presumptive Palpsmentioning
confidence: 98%
“…Specifically, we showed that perturbation of FGF-MAPK signaling led to ectopic FoxC expression, but larvae that developed under these conditions failed to develop palps. A recent study revealed that, whereas FoxC is a marker of the palp lineage, it is not a marker of palp fate; FoxC expression in the palp lineage persists under conditions that inhibit palp development (Ikeda et al, 2013). Moreover, Islet expression is lost upon MAPK inhibition from the 8-cell stage onward, and MAPK signaling through the neurula stage is reported to be required for normal palp development (Hudson et al, 2003).…”
Section: Fgf-mapk Signaling Is Required For Proper Islet Patterningmentioning
confidence: 99%
See 1 more Smart Citation